Critique on the conceptual developments of innovative practices with lightweight fills - Wijeyesekera, Devapriya Chitral; Ratha, Nurvin; Lim, Alvin John Meng Siang (EDP Sciences, 2017)
Conceptual developments are underpinned by the intellectual process of constant reviewing and developing innovative research ideas into realistic design. There exists no one quick fix, fit for purpose solution to ensure stability of structures being constructed on a wide range of demanding ground conditions and variety of project constraints. Routine highway design and construction technology conformingly adopt only conventional fill methods and thus fail even to address adequately the less favoured conditions in challenging situations: a high initial construction cost arising from a full replacement of existing unfavourable soil conditions or an unsustainable construction design leading to a condition of rapid disintegration requiring regular expensive and disruptive highway maintenance activity. Undulating road embankment surfaces result from the transference of heavy self-weight of the embankment fill on yielding and non-uniform subgrade such as in peat soils. The Manitoba Water Services Board [1] specifies four classes of fills (viz; common, compacted common, compacted select granular backfill and unshrinkable backfill) for backfilling of pipeline trenches. Both conventional and alternatively sustainable backfills are discussed in this paper with new and appropriate technology opening doors with other tangible benefits for innovative and cost saving outcomes for differing construction scenarios.